Empowering people towards sustainable development: hope and despair of e-governance application in third world countries - Tharmini, N. (university of Jaffna, 2014)
Increasingly, governments in the Third Word countries are keen in the application of e governance with their sustainable development goals. These Applications is said to have an effect on empowerment, poverty reduction and improving government responsiveness to poor community who have had little prior access to public services. However, this paper indentifies a few benefits that have been realized between hope and despair. In general, the lack of resources and technical capacity has meant that e-governance applications cannot be scaled easily. The list of applications can be divided into three broad categories: (a) delivering information and transactions services to citizens, (b) delivering services to business and industry and increased efficiency within the government, and (c) delivering services to internal clients. Several e-governance projects have failed because they were not aligned with realistic expectations and the willingness of governments to introduce basic reform. A reform agenda needs to be encouraged more broadly and e-governance cannot be perceived as a panacea or the driver of the reform. This collateral and explorative attempt projects the major trends and issues in the application of e-governance relating to empowering people towards sustainable development in Third World Countries.
Keywords: Third world; Poverty; Community